Pertentangan antara Wahyu dan Akal sebagai al-Dakhīl dalam Tafsir: Kajian terhadap Kitab Dar’ Ta‘āruḍ Karya Ibn Taymiyah - Anillahi Ilham Akbar; Abdul Kadir Riyadi (Institut Agama Islam Negeri (IAIN) Keiri, 2022)
The relevance of revelation and sense especially regarding the contradiction between the two is a problem that is often discussed by Muslim intellectual. Most of the scholars tend to reject the existence of a contradiction between revelation and sense, they argue that it should be so because basically they both come from the Almighty God, so it is impossible for the two to be contradictory. This of course will affect the authenticity of the resulting interpretation and will cause defects in it. Based on this, intellectual anxiety arises about how the scholars respond to this matter, which in this study will be devoted to the response of Ibn Taymiyah in his book Dar’ Ta'āruḍ al-'Aql wa al-Naql, and how its relevance to the concept of al-dakhīl (infiltration) in the interpretation of the Qur'an. This study is a literature review by examining the book Dar’ Ta'āruḍ al-'Aql wa al-Naql by Ibn Taymiyyah and several writings related to this topic. This results in an understanding that the assumptions that say there is a contradiction between revelation and sense in the book are unacceptable. Ibn Taymiyah also emphasized that although it was forced to be possible for a conflict between the two to occur, the conflict that occurred was on the status of dalīl that was qaṭ'ī-ẓannī, not on its status as revelation and sense. The contradiction that occurs between revelation and sense can ultimately be categorized as al-dakhīl fī al-tafsīr, as one of the factors that causes the authenticity of interpretation to disappear.